FoxO3 deficiency in cortical astrocytes leads to impaired lipid metabolism and aggravated amyloid pathology. Issue 8 (11th July 2021) - Du, Shuqi; Jin, Feng; Maneix, Laure; Gedam, Manasee; Xu, Yin; Catic, Andre; Wang, Meng C.; Zheng, Hui
Abstract: The rise of life expectancy of the human population is accompanied by the drastic increases of age‐associated diseases, in particular Alzheimer's disease (AD), and underscores the need to understand how aging influences AD development. The Forkhead box O transcription factor 3 (FoxO3) is known to mediate aging and longevity downstream of insulin/insulin‐like growth factor signaling across species. However, its function in the adult brain under physiological and pathological conditions is less understood. Here, we report a region and cell‐type‐specific regulation of FoxO3 in the central nervous system (CNS). We found that FoxO3 protein levels were reduced in the cortex, but not hippocampus, of aged mice. FoxO3 was responsive to insulin/AKT signaling in astrocytes, but not neurons. Using CNS Foxo3 ‐deficient mice, we reveal that loss of FoxO3 led to cortical astrogliosis and altered lipid metabolism. This is associated with impaired metabolic homoeostasis and β‐amyloid (Aβ) uptake in primary astrocyte cultures. These phenotypes can be reversed by expressing a constitutively active FOXO3 but not a FOXO3 mutant lacking the transactivation domain. Loss of FoxO3 in 5xFAD mice led to exacerbated Aβ pathology and synapse loss and altered local response of astrocytes and microglia in the vicinity of Aβ plaques. Astrocyte‐specific overexpression of FOXO3 displayed opposite effects, suggesting that FoxO3 functions cell autonomously to mediate astrocyte activity and also interacts with microglia to address Aβ pathology. Our studies support a protective role of astroglial FoxO3 against brain aging and AD. Abstract : FoxO3 expression decreases with aging. CNS‐specific FoxO3 deficiency leads to aberrant cortical astrocyte activation. This is associated with metabolic defects in mitochondrial respiration, lipid consumption, and reduced Aβ uptake capacity. In an AD mouse model, loss of FoxO3 aggravates Aβ pathology while astrocytic FoxO3 overexpression significantly reduces the amyloid burden.